The Creative Process in Theatrical Play Production: From Conception to Performance - Obado Tunde Oliogu (CV Projurnal Mitra Publikasi, 2025)
Production of theatrical plays is a creative endeavour that involves a complex process that develops from the first idea to the performance on the stage. This paper looks at the systematic process that exists in bringing a dramatic vision to theatrical reality, and the dynamic interplay between imagination, planning, collaboration, and execution. The study takes a qualitative and descriptive approach that combines literature on play production processes with case experiences from contemporary theatre practice in Nigeria and outside. Research indicates that the creative process usually happens through ideas generation, script development, casting, design, rehearsal and performance, where each phase involves specific skills and a need for co-operation from directors, actors, designers and technical teams. On the basis of the thesis that successful play production depends on effective coordination of artistic creativity and managerial discipline, the paper posits that audience engagement is the ultimate criterion of theatrical effectiveness, as it constitutes the representative sample of the play. Finally, it highlights the importance of innovation, collaboration, and adaptability in remaining relevant in an ever-evolving entertainment landscape. Recommendations are provided on how to enhance creative cooperation, invest in technical capacities and promote cultural specificity in productions to enrich the theatrical experience and ensure the vitality of the live performance form.